Expanding Legal Standing in Political Party Dissolution Disputes in Indonesia - Muhamad Islahudin Azhari; Ahmad Ahmad; Muhammad Rizqi Ramadhan; Gamal Abdul Nasir; Fajar Sulistyo (Indonesian Journal of Law and Policy Studies, 2024)
The dissolution of political parties is a constitutional mechanism intended to uphold democracy, constitutionalism, and the principle of the rule of law. The Constitution grants the Constitutional Court the authority to decide on cases of dissolution of political parties, but the provisions of the Law on the Constitutional Court limit the right to submit petitions to the government only. This provision creates problems in practice, especially when allegations of serious violations committed by political parties that have a broad impact on the democratic system are not followed by a petition for dissolution. This study aims to examine the urgency of expanding the subject of petitioners in cases of dissolution of political parties, formulate more comprehensive criteria regarding the grounds for dissolution, and analyze the implications of this limitation on the principles of democracy in Indonesia. This study uses normative legal methods with statutory, philosophical, and sociological approaches. The results show that limiting petitioners to the government has the potential to create conflicts of interest and weaken the oversight function of political parties. Therefore, it is necessary to expand legal standing to other parties, such as election supervisory institutions and the public, and expand the grounds for dissolution to include serious violations of democracy and election law, in order to strengthen political party accountability and consolidate constitutional democracy in Indonesia